A new species of the genus Eirenis Jan, 1863 (Squamata: Colubridae) from Kerman Province in South-central Iran - Akbarpour, Morteza; Rastegar-Pouyani, Nasrullah; Fathinia, Behzad; Rastegar-Pouyani, Eskandar (Zootaxa, 2020)
A new species of Dwarf Snakes, Eirenis rafsanjanicus sp. n., is described from south-central Iran. This species is well distinguished from other congeners in both molecular and morphological characters, and its description increases the number of described Eirenis species to 26. Eirenis rafsanjanicus sp. n. is genetically closest (6% in Cytb) to the recently described E. yassujicus, which inhabits high habitats in southern Iran. Morphologically, E. rafsanjanicus sp. n. is more similar to E. modestus than to other congeners. A revised key to the genus is presented.